Talking about human papillomavirus and cancer: protocol for a patient-centred study to develop scripted consultations. Issue 4 (25th April 2016) - Hendry, Maggie; Pasterfield, Di; Adams, Richard; Evans, Mererid; Fiander, Alison; Robling, Michael; Campbell, Christine; Makin, Matthew; Gollins, Simon; Hiscock, Julia; Nafees, Sadia; Bekkers, Marie-Jet; et al.
Abstract : Introduction: Persistent infection with sexually transmitted, high-risk human papillomavirus (HPV) types is the cause of all cervical cancers and some anogenital and oropharyngeal cancers. HPV is an extremely common asymptomatic infection but little known and poorly understood by the public. Patients with HPV-related cancers have new and challenging information needs due to the complex natural history of HPV and the stigma of sexual transmission. They may ask questions that are outside the remit of the traditional cancer consultation, and there is a lack of guidance on how to counsel them. This study aims to fulfil that need by developing and testing cancer site-specific scripted consultations. Methods and analysis: A synthesis of findings generated from previous work, a systematic review of information-based interventions for patients with HPV-related cancers, and interviews with cancer clinicians will provide the evidence base underpinning provisional messages. These will be explored in three phases of face-to-face interviews with 75–90 purposively selected patients recruited in cancer clinics to: (1) select and prioritise the most salient messages, (2) phrase the messages appropriately in plain English and, (3) test their acceptability and usefulness. Phases 1 and 2 will draw on card-sorting methods used in website design. In phase three, we will create cancer site-specific versions of the script and test them using cognitive interviewing techniques. Ethics and dissemination: The study has received ethical approval. Findings will be published in a peer-reviewed journal. The final product will be cancer-specific scripted consultations, most likely in the form of a two-sided information sheet with the most important messages to be conveyed in a consultation on one side, and frequently asked questions for later reading on the reverse. However, they will also be appropriate and readily adaptable to web-based uses.